SISTEM INFORMASI PETA DIGITAL LOKASI KOS DI KOTA PADANG MENGGUNAKAN GOOGLE MAP API V3 BERBASIS FRAMEWORK CODEIGNITER - Indra Rozi; Asrul Huda; Oktoria Oktoria (Universitas Negeri Padang, 2015)
The development ofboarding house geographic information system (GIS) ismotivated by the lack of information obtained by students about boarding house who was studying in Padang city. The owner of boarding house do promotions using pamphlet or flyer. That is causing inefficient access for people or students who need this informations because it can not be accessed anytime and anywhere. The purpose of making this final project usinggeographic information systemis to design an integrated information system to ease people especially students obtain information boarding house including facilities available in Padang city. The system is designed to be easily and efficiently accessed through desktop and mobile device.This information system design using the UML (Unified Modelling Language) modelling visualization with some object-oriented visualization diagram. The programming language that is used to develop this geographic information system is PHP (PHP Hypertext Preprocessor) based codeigniter framework, Javascript, AJAX, with MySQL as Database Management System (DBMS) and Sublime Text 3 as editor. This research are conducted to produce an applicative geographic information system that can be used to ease people or students to get information of boarding house along with tracking or direction with GPS, price, facilities inside, and transportation. Is is expected this information system can help the owner of boarding house to utilize technology as distribution information media and give ease to the people or students to get that information.Keywords:Geographic Information System (GIS), Boarding House, UML.